Answer:
b
Step-by-step explanation:
I did it
Answer:
![10x^{3} - 26x^{2} - 12x](https://tex.z-dn.net/?f=10x%5E%7B3%7D%20-%2026x%5E%7B2%7D%20-%2012x)
Step-by-step explanation:
1) Use the FOIL method: (a+b)(c+d)=ac+ad+bc+bd.
![10x^{3} - 30x^{2} + 4x^{2} -12x](https://tex.z-dn.net/?f=10x%5E%7B3%7D%20-%2030x%5E%7B2%7D%20%2B%204x%5E%7B2%7D%20-12x)
2) Collect like terms.
![10x^{3} + (-30x^{2} +4x^{2} )-12x](https://tex.z-dn.net/?f=10x%5E%7B3%7D%20%2B%20%28-30x%5E%7B2%7D%20%2B4x%5E%7B2%7D%20%29-12x)
3) Simplify.
![10x^{3} - 26x^{2} -12x](https://tex.z-dn.net/?f=10x%5E%7B3%7D%20-%2026x%5E%7B2%7D%20-12x)
Therefor, the answer is, 10x^3 - 26x^2 - 12x.
Answer:
1. 75%
2. 20%
3. 20%
4. decrease 5.4%
Step-by-step explanation:
1. 119-68=51, 51/68=0.75
2. 30-24=6, 6/30=0.20
3. 18-15=3, 3/15=0.20
4. 762-721=41, 41/762=0.0538
Answer:
a 1/ (6^2)
Step-by-step explanation:
6^3 / 6^6
when dividing exponents we can subtract
6^ (3-6)
6^(-3)
negative exponents go from the numerator to the denominator
1/ (6^3) = 1/216 = 6^-3
1/6^2 is not equal
Answer:
2xy - 6x +2y
Step-by-step explanation:
12xy - 10xy = 2xy
5y - 3y = 2y
2xy - 6x + 2y